CINEMA AFRICA 2021 - In Conversation with Emmanuel Parraud (Cinema Africa 2021, 2022)
In the german city of Bayreuth, during the winter of 2021, the 13th edition of the CINEMA AFRICA film festival took place. Despite the ongoing pandemic, the team of the Africa Multiple Cluster of Excellence and a group of filmmakers from different corners of the globe were able to showcase five films, that truly showcased the artistic diversity of modern day African filmmaking. With a regional focus on the Indian Ocean, last year's films took us from Tanzania and South Africa to La Réunion and Mauritius, creating a space for stories once overlooked and untold. During the filmmakers' short stay in Bayreuth, we, the Cluster of Excellence, were able to sit down with each filmmaker to talk about her/his respective works. In this video Interview Prof. Dr. Ute Fendler and Mr. Thierry Boudjekeu talk with French filmmaker Emmanuel Parraud about his two showcased films: Maudit! and Sac la Mort. Amongst other things, the filmmaker talks about making films in Creole. You can find Mr Parraud on Instagram: https://www.instagram.com/emmanuelparraud/ CINEMA AFRICA 2021 Trailer: https://youtu.be/ic2xULGVZ5A Cinema Africa Interviews: https://youtube.com/playlist?list=PLDlHB4qY36Wi8VczSMvmrDs1zFXoRRh0- Thanks for Watching!